Bandongan-Based Arabic Learning and Students’ Reading Improvement in Islamic Boarding Schools - Sofin Murtiha; Muhammad Rizal Shalahuddin (Golden Ratio of Data in Summary, 2026)
This study examines the implementation of Bandongan-based Arabic learning to improve students’ Arabic reading skills in Islamic boarding schools. Using a qualitative case study approach at a pesantren in Pacitan, Indonesia, the research involved eighth-grade students, Arabic teachers, and administrators. Data were collected through observations, interviews, and documentation, then analyzed using data reduction, display, and conclusion drawing techniques. The findings show that the Bandongan method improves students’ reading fluency, vocabulary mastery, pronunciation accuracy, and comprehension of classical Arabic texts. The method also enhances discipline, listening skills, concentration, and collaborative learning. Furthermore, integrating kitab kuning traditions into modern Arabic instruction creates contextual and culturally rooted learning experiences. This study demonstrates that traditional Islamic learning methods remain relevant and effective in contemporary Arabic language education.